A Co-creation Centre for Accessible Rehabilitation Technology - Kerr, Andy; Grealy, Madeleine Ann; Kuschmann, Anja; Rutherford, Rosie; Rowe, Philip (Frontiers in Rehabilitation Sciences, 2022)
Background The prevalence of disabling conditions is increasing globally. Rehabilitation, applied intensively, improves function. Internationally the workforce is not sufficient to deliver intensive rehabilitation. Technology offers solutions, however, barriers such as cost, training, size and poor design limit access. Our group of engineers and researchers have established a centre dedicated to developing accessible technology through frequent user engagement. Methods A co-creation model, coupling engineering and science with user experience and industrial partnerships, is used to develop new technology. Due to the complexity and prevalence the focus is stroke. Participants, with a wide range of disabilities, attend the centre 2/3 times per week for eight weeks and use prototype and commercial technology (de-weighting systems, neurostimulation, virtual reality, treadmills, bespoke rehab games, communication apps, powered exercise equipment and gamified resistance equipment) with supervision. Standard outcome measures are recorded before, immediately after, and 3 months post programme and are used in combination with participant interviews to design and review the rehabilitation programme. Qualitative methods (surveys and interviews) capture personal experiences with the technology and an advisory group (stroke survivors) help interpret findings for the design process. A pilot study, investigating acceptability and feasibility, is currently underway and due to report findings in 2022. Discussion A new research and engineering centre dedicated to developing accessible rehabilitation technology is currently undergoing acceptability and feasibility testing with stroke survivors. The centre, through close and frequent engagement with users and industry, has the potential to transform rehabilitation technology and help revolutionise the way rehabilitation is delivered.